Extended oral antibiotics fail to reduce surgical site infection in orthopedic surgeries: A comparative study - Alireza Mirahmadi; Pooya Hosseini-Monfared; Mehrdad Farrokhi; Raza Minaie; Amin Bateni; Seyed Morteza Kazemi (PLoS ONE, 2025)
Background Surgical site infection (SSI) is associated with a significant burden in orthopedic surgeries, leading to increased morbidity, prolonged hospital stays, and higher healthcare costs. Despite the widespread use of prophylactic antibiotics to reduce the risk of infection, the optimal duration for antibiotic administration remains controversial. Newer studies reported controversial results compared to existing guidelines; therefore, we aimed to compare the efficacy and post-operative complications of short-term (<24 hours) and extended oral antibiotics in reducing infection rates following orthopedic surgeries. Methods In this retrospective study, patients who underwent orthopedic surgeries, including total knee arthroplasty (TKA), total hip arthroplasty (THA), anterior cruciate ligament (ACL) reconstruction, and hip internal fixation, were recruited from the hospital data registry. Patients were divided into two groups of short-term (<24 hours) and extended oral antibiotics groups based on the duration of prophylactic antibiotic use. The infection rate during three months after the surgery and the incidence of antibiotic-related adverse events were compared between the groups. Results Of the 398 patients in the study, 246 received short-term, and 152 received extended oral antibiotics. There was no significant difference between the short-term (2.8%) and extended (4.6%) groups with respect to the rate of SSI (P = 0.35). The patients in the extended antibiotic group demonstrated more post-operative complications compared to the short-term group (36.2% Vs. 22.8%, P = 0.004). Conclusion Our findings demonstrated that extended oral antibiotics did not reduce the rate of SSI following orthopedic surgeries compared to short-term prophylaxis. Furthermore, patients who received prolonged antibiotic demonstrated a higher incidence of postoperative complications. Our study supports the recommendation not to use extended prophylactic oral antibiotics over 24 hours in orthopedic surgeries.